The protective effects of oral low-dose quercetin on diabetic nephropathy in hypercholesterolemic mice - Gomes, Isabele B.; Porto, Marcella L.; Santos, Maria Carmen L.; Campagnaro, Bianca P.; Gava, Agata L.; Meyrelles, Silvana S.; Pereira, Thiago M.; Vasquez, Elisardo C. (Frontiers in Physiology, 2015)
Aims: Diabetic nephropathy (DN) is one of the major causes of end-stage renal disease, and the incidence of DN is increasing worldwide. Considering our previous report indicating that chronic treatment with oral low-dose quercetin (10 mg/Kg) demonstrated renoprotective, anti-oxidative and anti-apoptotic effects in the C57BL/6J model of diabetic nephropathy, we investigated whether this flavonoid could also have beneficial effects in concurrent DN and spontaneous atherosclerosis using the apolipoprotein E-deficient mouse (apoE-/-). Methods: DN was induced by streptozotocin (100 mg/kg/day, for 3 days) in adult apoE-/-mice. Six weeks later, the mice were divided into the following groups: diabetic apoE-/- mice treated with quercetin (DQ, 10 mg/kg/day, 4 weeks), diabetic ApoE-/- mice treated with vehicle (DV) and non-treated non-diabetic (ND) mice. Results: Quercetin treatment caused a reduction in polyuria ( 30%), glycemia ( 25%), abolished the hypertriglyceridemia and had significant effects on renal function, including decreased proteinuria ( 15%) and creatininemia ( 30%), which were accompanied by beneficial effects on the renal structural changes, including normalization of the index of glomerulosclerosis and kidney weight. Conclusions: Our data revealed that quercetin treatment significantly reduced DN in hypercholesterolemic mice by inducing biochemical and morphological modifications. Thus, this translational study highlights the importance of quercetin as a potential nutraceutical for the management of DN, including in diabetes associated with dyslipidemia.